1998
DOI: 10.1016/s0008-6363(98)00028-5
|View full text |Cite
|
Sign up to set email alerts
|

Myofilament calcium sensitivity is decreased in skinned cardiac fibres of endotoxin-treated rabbits

Abstract: Objective: The aim was to determine whether myofilament Ca 2q sensitivity is altered in skinned cardiac fibres from endotoxin-treated Ž .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 31 publications
7
22
0
1
Order By: Relevance
“…In line with these findings, myocardial L-type calcium channels have been found to be decreased during endotoxemia (63). Second, a reduction in myofilament calcium sensitivity has been reported in endotoxemic rabbits (64,65). The exact mechanisms of these observations are only partially understood, but the decreased response of myofilaments to calcium may be involved in the impaired myocardial contractility and depression of systolic function in septic patients.…”
Section: Calcium Flux and Cardiomyofilamentsmentioning
confidence: 58%
“…In line with these findings, myocardial L-type calcium channels have been found to be decreased during endotoxemia (63). Second, a reduction in myofilament calcium sensitivity has been reported in endotoxemic rabbits (64,65). The exact mechanisms of these observations are only partially understood, but the decreased response of myofilaments to calcium may be involved in the impaired myocardial contractility and depression of systolic function in septic patients.…”
Section: Calcium Flux and Cardiomyofilamentsmentioning
confidence: 58%
“…A mechanism similar to that found for IL-1 in muscle (220) or in cerebro-microvascular endothelial cells (645) might be possible where endotoxin could enter through local membrane defects, e.g., also induced by NOS activation (427,673). Probably more important are subsequent inflammatory reactions induced by endotoxin in the tissue, i.e., immune activation of macrophages and release of pro-inflammatory cytokines that provide the grounds for subsequent alterations of contractile performance (692). During endotoxin shock, large amounts of NO, either released by endothelial cells but also by myocytes, seem to be causative for a deregulation of thin filament troponins by raising cGMP and phosphorylation of troponins by cGMP-dependent protein kinases, at least in the heart (75,629,673,693,791).…”
Section: Ca 2؉ Regulation Of the Contractile Apparatus In Criticalmentioning
confidence: 83%
“…However, another study in endotoxin-treated rabbits showed higher Ca 50 values for half-activation of papillary muscle isometric force (1.78 vs. 1.53 M) already 4 h after a 0.5 mg/kg iv endotoxin treatment, indicating a reduced myofibrillar Ca 2ϩ sensitivity. The latter even worsened after a higher LPS dose (1 mg/kg: Ca 50 ϭ 2.08 M) and with time (2.12 M after 24 h) but returned to normal after 5 days (692). Treatment of control papillary muscle strips with isoproterenol produced a reduction in myofibrillar Ca 2ϩ sensitivity similar to that seen in LPS-treated preparations, indicating a higher degree of protein kinase A-dependent phosphorylation as a cause for the changes in Ca 2ϩ sensitivity seen in septic hearts (693).…”
Section: B Altered Global Muscle Ca 2؉ Homeostasis In Critical Illnessmentioning
confidence: 95%
“…Whether these findings might have an impact on organ function or integrity remains unknown. However, it is of interest that cardiac dysfunction (suppressed Ca 2ϩ sensitivity with decreased contractility [12,13]) and lung injury (acute respiratory distress syndrome) are commonplace in sepsis syndrome. This raises the intriguing but highly speculative question of whether tissue Fe loading potentially could worsen clinical sepsis syndrome or outcomes.…”
Section: Sites Of Fe-mediated Tnf-␣ Productionmentioning
confidence: 99%